Association of remote work with tobacco and alcohol use: a cross-sectional study in Japan - Kento Sonoda; Sumiyo Okawa; Takahiro Tabuchi (BMC Public Health)
Abstract Background Remote work allows one to work free from workplace policy, but it may negatively affect health-related behaviors such as tobacco product use and alcohol drinking. Our study aimed to investigate the association of remote work with tobacco dependence and hazardous alcohol use. Methods This nationwide Internet-based survey was conducted in Japan in February 2023. Using the data of 8,292 workers aged 18 – 64, frequency of remote work (0, < 1, ≥ 1 day per week), tobacco dependence based on the scores of the Tobacco Dependence Screener ≥ 5, hazardous alcohol use based on the scores of the Alcohol Use Disorders Identification Test ≥ 8 were assessed. Then, the associations of frequency of remote work with tobacco dependence and hazardous alcohol use were examined using a multivariable Poisson regression model. Results The percentages of remote work 0, < 1, ≥ 1 day per week were 56.6%, 9.9%, and 33.5%, respectively, whereas those of tobacco dependency and hazardous alcohol use were 11.3% and 17.9%, respectively. Remote work < 1 day per week (adjusted prevalence ratio [aPR] 1.30, 95%CI 1.07 – 1.57), and ≥ 1 per week (aPR 1.29, 95%CI 1.13 – 1.47) were associated with tobacco dependence. Further, remote work < 1 day per week (aPR 1.43, 95%CI 1.25 – 1.65), and ≥ 1 per week (aPR 1.40, 95%CI 1.27 – 1.55) were associated with hazardous alcohol use. Conclusions Remote workers showed higher prevalence of tobacco dependence and hazardous alcohol use. The health behavior of remote workers should be carefully monitored.